Administration of non-contentious estates in west Malaysia: legal and administrative reforms - Arshad, Azhani; Halim, Akmal Hidayah (Panoply Consultancy, 2015)
In West Malaysia, the structure and procedures for estates administration were originally initiated during the colonial period. At present, the jurisdiction to administer the deceased’s estates lies with the High Court, the Small Estates Distribution Section and the Public Trust Corporation (Amanah Raya Berhad) depending on the types of estates left by the deceased and governed by various statutes of general application, namely, the Rules of Court 2012, the Probate and Administration Act 1959, the Small Estates (Distribution) Act 1955 and the Public Trust Corporation Act 1995. These various administrative bodies, estates and statutes have resulted in the non-uniformity, uncertainty and inconsistency of the laws and procedures applicable to the administration of estates. Hence, reforming the existing legal framework for the administration of the deceased’s estates has become highly necessary. In pursuant thereto, this research analyses the emerging legal and administrative issues in the administration of the deceased’s estates in West Malaysia based on the analysis of the governing statutes, reported cases, interviews conducted with various individuals and groups, and data obtained from the respective administrative bodies. This research finds that reform should be made to the existing law and administrative institution in order to regulate the law and procedure on the administration of non-contentious estates in West Malaysia. The research also finds that there should only be a single administrative body to deal with estate administration particularly for the non-contentious estate proceeding.